More tolerant than expected: Taking into account the ability of Cladonia portentosa to cope with increased nitrogen availability in environmental policy. (December 2020) - Munzi, S.; Cruz, C.; Branquinho, C.; Cai, G.; Faleri, C.; Parrotta, L.; Bini, L.; Gagliardi, A.; Leith, I.D.; Sheppard, L.J.
Graphical abstract: Highlights: Cladonia portentosa can cope with long-term exposure to nitrogen. Cladonia 's tolerance must be considered when setting nitrogen Critical Loads. Short- and long-term exposure to nitrogen activate the same molecular response. Maintaining stable pH value is a protection mechanism when exposed to ammonium. Abstract: The lichen Cladonia portentosa is generally considered to be sensitive to increased environmental nitrogen (N) deposition. However, the presence of this lichen in impacted environments suggests that it can cope with prolonged exposure to high N availability. To test the tolerance of this species to N, photosynthetic parameters, carbon and N concentrations and isotopic signature, chitin concentration, surface pH and extracellular enzymatic activity were measured in samples exposed for 11 years to different N doses and forms at the Whim bog N manipulation experimental site (United Kingdom). The results showed that C. portentosa is tolerant to long-term exposure to wet N deposition, maintaining its functionality with almost unaltered physiological parameters. The comparison of the proteome of short- and long-term exposed samples showed similar changes in protein expression suggesting that mechanisms to cope with N are not dependent on the exposure time even after more than a decade. Since empirical N Critical Loads are based on the response of sensitive components of the ecosystem, like C. portentosa, its capacity to cope with short- and long-term exposure to N needs to be recognized and taken into account when setting them, likewise, the significance of the form of N. Capsule: Updated knowledge on tolerance of sensitive species to nitrogen must be taken into account to establish environmental policy.